Características morfo-fisiológicas como determinantes da capacidade de manutenção de territórios em machos de Macrothemis imitans (Odonata: Libellulidae) - Mourão, Marco Antônio Nogueira (2012)
In many animal species, males fight for the possession of territories that increase their mating chances. The fighting behavior of males may range from conflicts without physical contact to disputes with injuries and possible deaths. There are three models aiming to explain the rules adopted by males to decide the winner of a contest: war of attrition (WOA), sequential assessment model (SAM) and cumulative assessment model (ACM). However, to be able to test these models it is necessary to identify male traits functionally related to fighting ability (RHP). In this sense, we used males of the dragonfly Macrothemis imitans to evaluate two hypotheses: 1) if contests occur with physical contact, traits related to the size define RHP and 2) if disputes occur without physical contact, traits which confer endurance define male RHP. We did field experiments during campaigns with two consecutive days. In each campaign we captured, marked, made behavioral observations and recaptured males that were defending a territorial site (resident males) and males that stablished territories in this sites after the experimental removal of the resident male (substitute males). After recapturing, we transported all males them to lab to measure total wing area, male fresh weight, muscle mass and fat content.The results indicated that resident males presented higher muscle mass and probably fat content than substitute males. Since disputes occurred with physical contact, these differences in muscle mass and fat content indicate that the functional relationship between fight behavior and traits linked to RHP should be rejected. Alternativelly, it is possible that the higher muscle mass confers higher ability to cause injuries or to avoid damage accrual.